Upaya Guru PAI dalam Meningkatkan Self Control pada Siswa di SMPN 7 Bukittinggi - Suzan, Wahyudi Faraz; Yarni, Linda; Ilmi, Darul; Jasmienti, Jasmienti (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This research is motivated by adolescence, especially the junior high school level, students are in a transition period that is vulnerable to various problems that often arise in students, including the lack of ability to control emotions, such as irritability, impulsivity, and difficulty in making wise decisions. This study aims to describe and analyze the efforts made by Islamic Religious Education (PAI) teachers in improving self-control in students at SMPN 7 Bukittinggi.This research is a qualitative study that uses the type of field research or field research. Key informants are 3 PAI teachers and supporting informants of class VIII students. Data collection techniques were carried out through observation and interviews. Data analysis was carried out with data reduction steps, data presentation, and conclusion drawing. The results of his research are strengthening positive behavior, elimination, saturation, changing the stimulus environment, punishment.